2017
DOI: 10.1177/1744806917710779
|View full text |Cite
|
Sign up to set email alerts
|

Dietary constituent, decanoic acid suppresses the excitability of nociceptive trigeminal neuronal activity associated with hypoalgesia via muscarinic M2 receptor signaling

Abstract: BackgroundAlthough decanoic acid (DA) is thought to act as a muscarinic cholinergic agonist, effect of DA on nociceptive behavioral responses and the excitability of nociceptive neuronal activity under in vivo conditions remain to be determined. The aim of the present study, therefore, was to investigate whether in vivo acute administration of ointment containing DA affects the excitability of nociceptive trigeminal spinal nucleus caudalis (SpVc) neurons associated with hypoalgesia in naïve rats.ResultsAfter l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Another study showed membrane hyperpolarization after M 2 mAchRs stimulation via activation of low-threshold, voltage-operated K + channels in nucleus raphe magnus (NRM) neurons [47]. The present authors' recent in vivo electrophysiological and behavioral experiments showed that topical DA reversibly evoked transient mechanical hypoalgesia, presumably via the same mechanism described above in TG neurons [48,49]. Together, these data suggest that DA is a potential therapeutic CAM for treatment of trigeminal nociception (Fig.…”
Section: Modulatory Mechanism By Which Dietary Constituents Modulate supporting
confidence: 75%
See 1 more Smart Citation
“…Another study showed membrane hyperpolarization after M 2 mAchRs stimulation via activation of low-threshold, voltage-operated K + channels in nucleus raphe magnus (NRM) neurons [47]. The present authors' recent in vivo electrophysiological and behavioral experiments showed that topical DA reversibly evoked transient mechanical hypoalgesia, presumably via the same mechanism described above in TG neurons [48,49]. Together, these data suggest that DA is a potential therapeutic CAM for treatment of trigeminal nociception (Fig.…”
Section: Modulatory Mechanism By Which Dietary Constituents Modulate supporting
confidence: 75%
“…During action potential generation, voltage-gated Na + currents in trigeminal ganglia are inhibited by resveratrol and DHA applied locally (43,45), while voltage-gated K + currents in primary sensory neurons are potentiated by resveratrol and chlorogenic acid (44). Topical application of decanoic acid also induces mechanical hypoalgesia, which in turn suppresses trigeminal ganglia excitability through M2 mAchRs signaling, thereby stimulating membrane hyperpolarization (48,49) and inhibiting action potential firing rates discharged through nociceptive primary afferent fibers to the central terminal and nociceptive neurons in the SpVc. Systemic delivery of LA inhibits Ca 2+ currents in presynaptic terminals, while local administration of resveratrol suppresses glutamatergic-activated neurotransmission of SpVc neurons responding to nociceptive mechanical stimulation via the NMDA receptor.…”
Section: Central Mechanismmentioning
confidence: 99%
“…Therefore, we formulated an ointment for in vivo application of DA (Patent number: P2013-139421A, Japan), as described and defined previously. 11 …”
Section: Methodsmentioning
confidence: 99%
“…Electrophysiological recordings were conducted on 26 adult male Wistar rats weighing 230–310 g (18 rats: SpVc NS neurons; 8 rats: TG neurons), as previously described. 11 In brief, after anesthesia and maintenance with pentobarbital sodium through a cannula into the jugular veins, animals were placed in a stereotaxic apparatus for extracellular activity recordings of single SpVc neurons, according to the coordinates demonstrated by Paxinos and Watson, 16 using a glass micropipette filled with 2% pontamine sky blue and 0.5 M sodium acetate. 11 , 17 For recordings of single TG neurons, the rats underwent a craniotomy and hemispherectomy to expose the trigeminal ganglia, and the activity was recorded from the left side of the neurons, as described for the SpVc units.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation